Machine Learning Based Beamwidth Adaptation for mmWave Vehicular Communications - Manic, Setinder; Heng Foh, Chuan; Köse, Abdulkadir; Lee, Haeyoung; Leow, Chee Yen; Chatzimisios, Periklis; Suthaputchakun, Chakkaphong; Foh, Chuan Heng (Institute of Electrical and Electronics Engineers Inc., 2023)
The incorporation of mmWave technology in vehicular networks has unlocked a realm of possibilities, propelling the advancement of autonomous vehicles, enhancing interconnectedness, and facilitating communication for intelligent transportation systems (ITS). Despite these strides in connectivity, challenges such as high path-loss have arisen, impacting existing beam management procedures. This work aims to address this issue by improving beam management techniques, specifically focusing on enhancing the service time between vehicles and base stations through adaptive mmWave beamwidth adjustments, accomplished using a Contextual Multi-Armed Bandit Algorithm. By leveraging various conditions to train the ML agent of the Contextual Multi-Armed Bandit Algorithm, it seeks to learn about vehicle mobility profiles and optimize the usage of different antenna beamwidth settings to maximize seamless connection time. The extensive simulation results showcase the effectiveness of an adaptive beamwidth for mobility profiles, extending the connection time a vehicle experiences with a base station when compared to the existing strategies. © 2024 Elsevier B.V., All rights reserved.
IEEE Malaysia Communication Society and Vehicular Technology Society Joint Chapter (Com-VT)
Keywords: Beamwidth Adaptation; Mmwave; V2X; Antennas; Intelligent Systems; Intelligent Vehicle Highway Systems; Machine Learning; Millimeter Waves; Vehicle to Everything; Vehicle to Vehicle Communications; Vehicles; Beam Management; Beam Widths; Beamwidth Adaptation; Machine-Learning; Mm Waves; Mm-Wave Technology; Mobility Profiles; Multiarmed Bandits (Mabs); V2X; Vehicular Communications; Base Stations